2023
DOI: 10.1136/gpsych-2023-101133
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Life Gatekeeper suicide prevention training programme in China: a Delphi study

Chengxi Cai,
Chen Yin,
Yongsheng Tong
et al.

Abstract: BackgroundYouth suicide has been a pressing public mental health concern in China, yet there is a lack of gatekeeper intervention programmes developed locally to prevent suicide among Chinese adolescents.AimsThe current Delphi study was the first step in the systematic development of the Life Gatekeeper programme, the first gatekeeper programme to be developed locally in China that aims to equip teachers and parents with the knowledge, skills and ability to identify and intervene with students at high risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Therefore, these interventions could be integrated into mental health programmes in diverse settings, including regions affected by humanitarian crises, where such resources are often lacking. 59 Overall, our analysis confirms that IBIs are effective treatments with high levels of patient satisfaction. Lastly, despite promising results, the review also highlights the need for caution.…”
Section: Discussionsupporting
confidence: 69%
“…Therefore, these interventions could be integrated into mental health programmes in diverse settings, including regions affected by humanitarian crises, where such resources are often lacking. 59 Overall, our analysis confirms that IBIs are effective treatments with high levels of patient satisfaction. Lastly, despite promising results, the review also highlights the need for caution.…”
Section: Discussionsupporting
confidence: 69%
“…1 In China, the suicide attempt (SA) rate for adolescents with MD is 51.96%, 2 and over 500 000 adolescent SA are reported annually in the USA due to depression. 3 Risk factors for SA include gender, hormone levels, family conflict and, particularly, negative cognitive styles such as rumination. [2][3][4][5][6] Our recent study 2 has demonstrated a significant positive association between rumination and SA in adolescents with MD; rumination fully mediated the relationship between depression and SA.…”
Section: To the Editormentioning
confidence: 99%
“…3 Risk factors for SA include gender, hormone levels, family conflict and, particularly, negative cognitive styles such as rumination. [2][3][4][5][6] Our recent study 2 has demonstrated a significant positive association between rumination and SA in adolescents with MD; rumination fully mediated the relationship between depression and SA. Additionally, our previous finding has revealed a negative correlation between rumination and resilience and that resilience mediates the relationship between rumination and depression.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Adolescent suicide not only negatively impacts parents and families but also profoundly affects teachers and peers at school. 13 According to self-reported health, youth with bipolar disorder had poorer quality of life compared with healthy youth, youth with chronic conditions, youth with behavioural disorders and youth with other non-behavioural/non-emotional disorders. 14 Unfortunately, approximately only 56.1% of youth with bipolar disorder have received mental health services.…”
Section: Introductionmentioning
confidence: 99%